The Oxford handbook of publishing - Phillips, Angus, 1961-; Bhaskar, Michael (Oxford : Oxford University Press, 2019)
Publishing is one of the oldest and most influential businesses in the world. It remains an essential creative and knowledge industry, worth over $140 billion a year, which continues to shape our education and culture. Two trends make this a particularly exciting time. The first is the revolution in communications technology that has transformed what it means to publish; far from resting on their laurels and retreating into tradition, publishers are doing as they always have - staying on the cutting edge. The second is the growing body of academic work that studies publishing in its many forms. Both mean that there has never been a more important time to examine this essential practice and the current state of knowledge.
Copyright and Intellectual Property / Mira T. Sundara Rajan -- Publishing and Corporate Social Responsibility / Angus Phillips -- Organizational Structures in Publishing / Frania Hall -- Trade Publishing / John B. Thompson -- Academic Publishing / Samantha J. Rayner -- Educational Publishing / Miha Kovač, Mojca K. Šebart -- Marketing for Publishing / Alison Baverstock -- Rights / Lynette Owen -- Authorship / Simone Murray -- Reading / Adriaan van der Weel -- Libraries / Alex Holzman, Sarah Lippincott -- Publishing History / Alistair McCleery -- Bookselling / Niels Peter Thomas -- Book Design / Paul Luna -- Publishing and Technology / John Maxwell -- Networks / Carlos A. Scolari -- The Future of Publishing / Michael Bhaskar, Angus Phillips -- Introduction / Michael Bhaskar, Angus Phillips -- Publishing and Society / Elizabeth Le Roux -- Publishing and Culture / John Oakes -- Publishing and Information / Martin Paul Eve -- Curation in Publishing / Michael Bhaskar -- Economics of Publishing / Albert N. Greco -- The Strategy of Publishing / Albert N. Greco -- Globalization and Publishing / Miha Kovač, Rüdiger Wischenbart.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 7, 2019).
Keywords: Publishers and publishing